Mitochondria-Associated Membranes As Networking Platforms and Regulators of Cancer Cell Fate - Sassano, Maria Livia; van Vliet, Alexander R.; Agostinis, Patrizia (Frontiers in Oncology, 2017)
The tight cross talk between two essential organelles of the cell, the endoplasmic reticulum and mitochondria, is spatially and functionally regulated by specific microdomains known as the mitochondria-associated membranes or MAMs. MAMs are hot spots of Ca2+ transfer between the ER and mitochondria, and emerging data indicate their vital role in the regulation of fundamental physiological processes, chief among them mitochondria bioenergetics, proteostasis, cell death and autophagy. Moreover, and perhaps not surprisingly, it has become clear that signaling events regulated at the ER–mitochondria intersection coordinate key processes in oncogenesis and in the response of cancer cells to therapeutics. ER-mitochondria appositions have been shown to dynamically recruit oncogenes and tumor suppressors, modulating their activity and protein complex formation, adapt the bioenergetic demand of cancer cells and to regulate cell death pathways and redox signaling in cancer cells. In this review, we discuss some emerging players of the ER-mitochondria contact sites in mammalian cells, the key processes they regulate and recent evidence highlighting the role of MAMs in shaping cell-autonomous and non-autonomous signals that regulate cancer growth.